Investigating the Nexus of Climate Change and Agricultural Production in Nigeria - Gershon, Obindah; Mbajekwe, Chinua (International Journal of Energy Economics and Policy, 2020)
This study examined the relationship between climate change and agricultural production (crop and livestock) in Nigeria using time series data from 1981-2017. Variables used to depict climate change are mean annual rainfall, temperature and carbon dioxide emissions. Data on crop yield was collated for 17 major crops produced in Nigeria with the livestock production index of Nigeria. Econometric analysis was carried out using Autoregressive Distributed Lag (ARDL). The results showed that there is a long run relationship between climate change and crop production while no long run relationship exists between climate change and livestock production. Furthermore, evidence is provided that rainfall and CO2 emissions have a positive and significant effect on crop yield in the long run while temperature has a negative and significant effect on crop yield in the long run. It also was seen that four period lagged rainfall has a positive and significant effect on livestock production; two period lagged temperature had a negative significant effect and one period lagged CO2 emissions had a negative significant effect on livestock production in Nigeria. Consequently, policy recommendations are offered for the government to meet its sustainable development goals (SDGs). Keywords: Agriculture, CO2 Emissions, Climate Change, Sustainable Development Goals, Livestock Production JEL Classifications: Q54, Q15, Q56, Q18 DOI: https://doi.org/10.32479/ijeep.9843